ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA PRIODE 2019-2022 PADA PT GUDANG GARAM - Batubara, Wahyudi; Sipayung , Rizki Christian (Politeknik Negeri Ambon, 2023)
PT Gudang Garam Tbk is a company engaged in the manufacturing industry. Many companies are of the same type, so companies must continue to compete and maintain their businesses. The company's financial statements are the main source for conveying its financial information and other information to parties who need it. This study analyzes financial ratios and assesses company performance. The type of data that the author uses is external secondary data obtained from the Indonesia Stock Exchange (IDX). The research objective is to provide an overview of the state of the company's financial statements and to compare industry averages. From the analysis of financial statements, it can be seen whether the company is in good condition or not by using financial ratios such as the liquidity ratio to determine the company's ability to meet its current liabilities, the solvency ratio to determine the company's assets financed by total debt, the profitability ratio to determine the company's ability to generate profit, and the activity ratio to determine the company's ability to manage its assets.